The Developmental Regulator SEEDSTICK Controls Structural and Mechanical Properties of the Arabidopsis Seed Coat. Issue 10 (13th September 2016) - Ezquer, Ignacio; Mizzotti, Chiara; Nguema-Ona, Eric; Gotté, Maxime; Beauzamy, Léna; Viana, Vivian Ebeling; Dubrulle, Nelly; Costa de Oliveira, Antonio; Caporali, Elisabetta; Koroney, Abdoul-Salam; Boudaoud, Arezki; Driouich, Azeddine; et al.
Abstract : A molecular network controlled by STK regulates cell wall properties of the seed coat, showing that, in addition to specifying organ identity, the role of STK in seed development includes modification of the cell wall structure. Abstract: Although many transcription factors involved in cell wall morphogenesis have been identified and studied, it is still unknown how genetic and molecular regulation of cell wall biosynthesis is integrated into developmental programs. We demonstrate by molecular genetic studies that SEEDSTICK (STK), a transcription factor controlling ovule and seed integument identity, directly regulates PMEI6 and other genes involved in the biogenesis of the cellulose-pectin matrix of the cell wall. Based on atomic force microscopy, immunocytochemistry, and chemical analyses, we propose that structural modifications of the cell wall matrix in the stk mutant contribute to defects in mucilage release and seed germination under water-stress conditions. Our studies reveal a molecular network controlled by STK that regulates cell wall properties of the seed coat, demonstrating that developmental regulators controlling organ identity also coordinate specific aspects of cell wall characteristics.